Business, the environment and sustainability: an Islamic perspective - Mhd. Sarif, Suhaimi; Benjasom, Muhammad Husnee (2012)
This paper explores the roles and responsibilities of business toward protecting the natural environment as a mean to create and maintain business sustainability from an Islamic perspective. The ultimate aim of a business is to maximize profit within the legitimate means, which is the bottom line of a business. The business greediness to pursue maximum profitability has contributed significant degradation of the natural environment, global warming and the reduction of greenhouse gases. This situation leads to negative consequences to the human and non human well being as well as business sustainability. A business is sustainable when it secures its profitability interest along with protecting the interest of the stakeholders and the natural environment. Hence, policy makers and business leaders formulated policies and programs to protect and preserve the environment from further degradation to protect and preserve business sustainability. However, many countries and major industry players are reluctant to participate in the programs. The study offers an integrative framework of business, the natural environment and sustainability from Islamic perspective, with a special reference to the Islamic Jurisprudence of the environment (Fiqh al-Bi’ah fi al-Islam) by Mustafa Abu-Sway, particularly the relationship between human beings and the environment (vicegerency, subjection, and inhabitation). Since the nature of the study is explorative, the research design fits into the constructionism research paradigm. The use of qualitative personal interview with the relevant informants provide rich insights to the objective of the study. The study used note taking approach in the personal interview with 35 respondents, which comprised five policy makers, 10 business leaders, and 5 community leaders in Malaysia and Thailand to provide the insights on the roles and responsibilities of business sectors toward protecting the natural environment and whether they are convinced that this approach contributes to business sustainability. The results of the study showed insignificant difference despite different geographical and political administration between Thailand and Malaysia. Policy makers from both countries were convinced that business sectors should include the natural environmental protection agenda into the business policies as part of the corporate social responsibility. The community leaders from both countries concurred with the policy makers that the business sectors should be more proactive in protecting the natural environment despite the ultimate business responsibility. Nevertheless, business sectors disagreed to burden the business solely with the responsibility to protect the natural environment as the duty to protect the natural environment is collective duties and responsibilities. In fact, business managers have to fulfill economic and legal responsibilities to maximize the value of the shareholders. The feedback from the informants suggest that policy makers, community leaders and business owners should revisit two duties and responsibilities to protect the natural environment and business sustainability, namely “subjection” and “inhabitation.” However, the results are not generalizable due to inadequate insights about the duties and responsibilities to protect the natural environment and to gain sustainability in business from Islamic perspective